2015
DOI: 10.1007/s11547-015-0502-8
|View full text |Cite
|
Sign up to set email alerts
|

Crohn’s disease of the small bowel: evaluation of ileal inflammation by diffusion-weighted MR imaging and correlation with the Harvey-Bradshaw index

Abstract: DWI sequences may be useful in differentiating actively inflamed small bowel segments from normal small bowel in CD. Though partial, the correlation between DWI sequences and HBI confirms the utility of this technique in the study of patients with CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 29 publications
4
21
0
Order By: Relevance
“…This was associated with very good levels of intra-and inter-rater reliability of the technique. Notably, DWI-MR without intravenous contrast did not prove inferior to standard contrast-enhanced MR in evaluating CD-related small-bowel inflammation in a very recent prospective non-inferiority study [18], thus confirming the data deriving from a retrospective series (Table 1) [19]. The recently reported excellent agreement between DWI-MR results and the MaRIA index further supports the usefulness of this technique in the study of CD inflammatory status [20].…”
Section: Evaluation Of Disease Activitysupporting
confidence: 75%
“…This was associated with very good levels of intra-and inter-rater reliability of the technique. Notably, DWI-MR without intravenous contrast did not prove inferior to standard contrast-enhanced MR in evaluating CD-related small-bowel inflammation in a very recent prospective non-inferiority study [18], thus confirming the data deriving from a retrospective series (Table 1) [19]. The recently reported excellent agreement between DWI-MR results and the MaRIA index further supports the usefulness of this technique in the study of CD inflammatory status [20].…”
Section: Evaluation Of Disease Activitysupporting
confidence: 75%
“…The acquisition of sequences in apnea and the administration of an anti-peristaltic agent (N-butyl scopolamine) during the investigation contributed to further reduce motion artifacts. The choice of a high value of b (800 s/mm²) has minimized the effect of perfusion in DWI images [12,14,29].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies, all retrospective, with known or suspected Crohn's disease [11][12][13][14], have deter-mined the role of diffusionweighted sequences and ADC values in identifying intestinal inflammation. These have shown that DWI sequences can distinguish intestinal segments with active inflammation by normal loops and that ADC value of segments with active disease was significantly lower than healthy ileal loops.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The surgical physical examination has been considered the "gold standard" (sensitivity 99.8 %) for the identification of perianal fistulas in CD for years [7]. Actually, MRI has an increasingly important role in the evaluation of disease activity in CD and of complicated CD and is actually considered the gold standard and recommended during the initial diagnosis of perianal CD according to the ECCO guidelines; moreover, compared to endoanal ultrasound it is comparable for the evaluation of perianal fistulas and proved to be superior for discriminating between simple and complex disease compared to clinical assessment and anal endosonography [10,[30][31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%